The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1108/lodj-08-2019-0352
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional analysis of spiritual leadership, affective commitment and employees' creativity in South Korea

Abstract: PurposeThis study aims to examine the relationships between three dimensions – vision, hope/faith and altruistic love – of spiritual leadership and employees' creativity and to verify the mediating role of affective commitment in such relationships.Design/methodology/approachData were collected from 462 South Korean employees in diverse industries through self-reported questionnaires, and hypotheses were tested using hierarchical multiple regression analysis.FindingsThe authors found that vision, hope/faith an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 68 publications
5
31
0
4
Order By: Relevance
“…Hypothesis 2 and 3: Spiritual leadership has positive and significant effects on affective commitment and work engagement. These findings correlate with previous research by Jeon and Choi [72], they found a link between spiritual leadership and employee creativity. Their analysis found that employees' affective commitment is positively related to vision, hope/faith, and altruistic love.…”
Section: -Discussionsupporting
confidence: 92%
“…Hypothesis 2 and 3: Spiritual leadership has positive and significant effects on affective commitment and work engagement. These findings correlate with previous research by Jeon and Choi [72], they found a link between spiritual leadership and employee creativity. Their analysis found that employees' affective commitment is positively related to vision, hope/faith, and altruistic love.…”
Section: -Discussionsupporting
confidence: 92%
“…The study's results align with (Fry et al, 2005) research regarding the causal model of spiritual leadership theory, which revealed a positive relationship between the quality of spiritual leadership and spiritual survival with organizational outcomes, consisting of commitment and productivity. The same results were also uncovered by (Mansor et al, 2013), (Baykal, 2019), (Tsui et al, 2019), (Jeon & Choi, 2020), (Rumangkit, 2020), (Djaelani et al, 2021) that a significantly positive influence of spiritual leadership toward organizational commitment occured.…”
Section: Spiritual Leadership and Organizational Commitmentsupporting
confidence: 63%
“…If leaders and employees have good spiritual leadership, it will have a good effect on employee performance. This variable is based on previous research conducted by Ki Seok Jeon and Byoung Kwon Choi with the research title "Multidimensional Analysis of Spiritual Leadership, Affective Commitment and Employee Creativity in South Korea" (Jeon & Choi, 2020). Then based on previous research conducted by Jie Yang, Mingchao Chang, Zhihong Chen, Lulu Zhou and Jiangjiang Zhang with the research title "The Mediation Effect of Spiritual Leadership on Employee Innovative Behavior" (Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research by Ki Seok Jeon and Byoung Kwon Choi (2020), vision, hope/belief, and selfless love are positively related to employees. In comparison, the practical implications of these findings indicate that leaders need to understand the importance of vision, hope or belief and altruistic love for employees in formulating employee affective commitment and stimulating creativity (Jeon & Choi, 2020). Then Spiritual Leadership has a positive impact on employee behaviour innovation.…”
Section: Introductionmentioning
confidence: 96%